Integrative genomic analysis identifies key pathogenic mechanisms in primary mediastinal large B-cell lymphoma - Mottok, Anja; Hung, Stacy S; Chavez, Elizabeth A; Woolcock, Bruce; Telenius, Adèle; Chong, Lauren C; Meissner, Barbara; Nakamura, Hisae; Rushton, Christopher; Viganò, Elena; Sarkozy, Clementine; Gascoyne, Randy D; et al. (Blood, 2019)
Primary mediastinal large B-cell lymphoma (PMBL) represents a clinically and pathologically distinct subtype of large B-cell lymphomas. Furthermore, molecular studies, including global gene expression profiling, have provided evidence that PMBL is more closely related to classical Hodgkin lymphoma (cHL). Although targeted sequencing studies have revealed a number of mutations involved in PMBL pathogenesis, a comprehensive description of disease-associated genetic alterations and perturbed pathways is still lacking. Here, we performed whole-exome sequencing of 95 PMBL tumors to inform on oncogenic driver genes and recurrent copy number alterations. The integration of somatic gene mutations with gene expression signatures provides further insights into genotype-phenotype interrelation in PMBL. We identified highly recurrent oncogenic mutations in the Janus kinase-signal transducer and activator of transcription and nuclear factor κB pathways, and provide additional evidence of the importance of immune evasion in PMBL ( and ). Our analyses highlight the interferon response factor (IRF) pathway as a putative novel hallmark with frequent alterations in multiple pathway members ( and ). In addition, our integrative analysis illustrates the importance of and mutations driving oncogenic signaling. The identified driver genes were significantly more frequently mutated in PMBL compared with diffuse large B-cell lymphoma, whereas only a limited number of genes were significantly different between PMBL and cHL, emphasizing the close relation between these entities. Our study, performed on a large cohort of PMBL, highlights the importance of distinctive genetic alterations for disease taxonomy with relevance for diagnostic evaluation and therapeutic decision-making.